Influence of Jahn-Teller active Mn3+ ions on electrical and dielectric properties, thermopower and Mössbauer spectra of rutile-type Fe1-xMnxNbTiO6 (0 ≤ x ≤ 0.9). (January 2019) - Günther, A.; Hochleitner, R.; Schmidbauer, E.; Schöttler-Himmel, A.; Volk, M.
Abstract: Various electrical and dielectric properties were measured on rutile-type compositions Fe1-x Mnx NbTiO6 (0 ≤ x ≤ 0.9) between ≈ 100 K and 750 K using impedance spectroscopy. DC conductivity σDC shows Arrhenius behavior for the bulk above room temperature (RT) for all x values. Starting from x = 0, there is a considerable change in activation energy EA and σDC (300 K) between x = 0.1 and 0.2 with increase from EA ≈ 0.3–0.6 eV, accompanied by a fall in σDC (300 K) from ≈10 −4 to 10 −8 Ω −1 cm −1 ; for x > 0.2 no considerable further variation with rising x is established. For x ≤ 0.1, below RT Mott's variable range hopping T −1/4 law is obeyed for σDC . The known relaxor-type behavior of the dielectric constant ε′ for x = 0 with very high peaks at 500–600 K for low frequencies (163 Hz-6 kHz) changes with rising x to consecutively lower values in ε′ with disappearance of the peaks and with the largest values at the highest applied temperatures; the relaxor-type behavior can originate from a combination of bulk, grain boundary and sample-electrode effects. Below RT, a dramatic decrease in ε′ is noted for low x values, resulting finally at ≈ 100 K for compositions of any x in the bulk value of ε' < 15. The thermopower above RT is negative, hence n-type conduction occurs and charge transport is attributed to small polaron hopping. 57 Fe Mössbauer parameters exhibit some irregularities between x = 0.05 and 0.2, ascribed predominantly to the influence of local distortions by Jahn-Teller active Mn 3+ ions. Highlights: Rutile-type Fe1-xMnxNbTiO6 (0 ≤ x ≤ 0.9) was synthesized in oxidizing atmosphere. Impedance spectra measured at low T enable to determine bulk properties. Electrical DC and AC conductivities show effect of Jahn-Teller active Mn 3+ . The dielectric constant ε′ shows relaxor-type behavior for small x values at high T. There is a considerable drop in ε ′for small x values at low T.